2018
DOI: 10.1136/bmjopen-2017-018541
|View full text |Cite
|
Sign up to set email alerts
|

Role of organisational factors on the ‘weekend effect’ in critically ill patients in Brazil: a retrospective cohort analysis

Abstract: IntroductionHigher mortality for patients admitted to intensive care units (ICUs) during the weekends has been occasionally reported with conflicting results that could be related to organisational factors. We investigated the effects of ICU organisational and staffing patterns on the potential association between weekend admission and outcomes in critically ill patients.MethodsWe included 59 614 patients admitted to 78 ICUs participating during 2013. We defined ‘weekend admission’ as any ICU admission from Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 29 publications
1
14
0
1
Order By: Relevance
“…This finding differs from other studies, in which longer times for processes performed at night and on weekends were observed, explained by fewer staff in those periods. ( 8 - 11 ) However, the of vacancy-to-occupancy time increased when the bed was offered on holidays, in line with the cited studies.…”
Section: Discussionsupporting
confidence: 72%
“…This finding differs from other studies, in which longer times for processes performed at night and on weekends were observed, explained by fewer staff in those periods. ( 8 - 11 ) However, the of vacancy-to-occupancy time increased when the bed was offered on holidays, in line with the cited studies.…”
Section: Discussionsupporting
confidence: 72%
“…The effect of weekend admission to ICU for patients suffering severe stroke on in-hospital mortality appears significant for our study population, notably persisting even when adjusting for type of stroke (in contrast to previous studies [7,14]). This outlines the potential effect of in-hospital factors on the 'weekend mortality effect', as alluded to by Zampieri and colleagues [11]. Further, the non-significant higher odds of in-ICU mortality for those admitted over the weekend demonstrates the potential influence of pre-hospital factors on ICU mortality for weekend admissions.…”
Section: Plos Onementioning
confidence: 69%
“…The present findings underline the particular need for urgent review and management of patients who suffer severe stroke of any kind, where delay may substantially affect outcomes more-so than for other patient sub-populations. Lower numbers of on-site senior staff, lower nurse-to-patient ratios, fewer standardized protocols, and subsequent delays to expert management [11], may have more serious ramifications for severe stroke patients, underlying a sub-population of critically ill patients who need particular care when admitted over the weekend. Our findings are relevant for all healthcare professionals working both in hospital, or on-call from home, responsible for such an at-risk patient population.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Intensive care unit (ICU) is a hospital ward where critically ill patients are closely monitored, generating a high granularity of data. Several healthcare processes have been analysed in the ICU, such as ICU admission outside daytime hours,7 weekend admission8 9 and the time of discharge 10. However, the healthcare processes of laboratory tests have not been investigated in ICU.…”
Section: Introductionmentioning
confidence: 99%